Bovine Genital Campylobacteriosis - Max B. Irsik; Jan K. Shearer (EDIS)
VM-166, a 3-page fact sheet by M.B. Irsik, DVM, MAB and J.K. Shearer, DVM, MS, describes this venereal disease of cattle formerly known as vibriosis, clinical findings and epidemiology, how to determine if there is a campylobacter problem in a herd, and the use of vaccines. Published by the UF Department of Veterinary Medicine -- Large Animal Clinical Sciences, March 2007.